(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
Neglected tropical diseases (NTDs) represent a significant global health challenge, particularly in regions with limited access to healthcare and sanitation facilities. India, with its vast population and diverse landscape, faces a substantial burden of NTDs, including lymphatic filariasis (LF), visceral leishmaniasis (VL), and dengue along with other coinfections. The Government of India has undertaken various initiatives to eliminate these diseases, aligning with global objectives. However, challenges persist, including the need for accurate disease burden estimation, resource allocation, and disease diagnosis.Efforts to eliminate NTDs in India require comprehensive strategies, including mass drug administration and vector control programs. Thus, accurate and accessible diagnostic tools are essential for disease surveillance and treatment monitoring. Point-of-care testing including molecular and serological-based techniques facilitates swift diagnosis and disease surveillance, particularly in resource-limited settings. Thus, by prioritizing investments in innovative diagnostic and therapeutic strategies, India can make significant strides toward improving patient survival and decrease mortality rates.